Respuesta :
The solutions of the system of equations are [tex](0,6)[/tex] and [tex](-2,0)[/tex]
Explanation:
Given that the system of equations are [tex]y = x^2 + 5x + 6[/tex] and [tex]y = 3x + 6[/tex]
We need to determine the solution to the system of equations.
Let us determine the solution to the system of equations using substitution method.
Thus, we have,
[tex]x^{2} +5x+6=3x+6[/tex]
Subtracting both sides of the equation by 6, we get,
[tex]x^{2} +5x=3x[/tex]
Subtracting both sides of the equation by 3x, we have,
[tex]x^{2} +2x=0[/tex]
Simplifying, we get,
[tex]x(x+2)=0[/tex]
Thus, the values of x are [tex]x=0[/tex] and [tex]x=-2[/tex]
Now, we shall determine the corresponding y - values.
Substituting [tex]x=0[/tex] in the equation [tex]y = 3x + 6[/tex], we get, [tex]y=6[/tex]
Similarly, substituting [tex]x=-2[/tex] in the equation [tex]y = 3x + 6[/tex], we get, [tex]y=0[/tex]
Therefore, the solution to the system of equations are [tex](0,6)[/tex] and [tex](-2,0)[/tex]
Answer:
(0,6) & (-2,0)
Step-by-step explanation:
y = x² + 5x + 6
y = 3x + 6
x² + 5x + 6 = 3x + 6
x² + 2x = 0
x(x + 2) = 0
x = 0, -2
x = 0, y = 3(0)+6 = 6
x = -2, y = 3(-2)+6 = 0